Low-Dose Acetylsalicylic Acid in Chronic Subdural Hematomas: A Neurosurgeon's Sword of Damocles - Mongardi, Lorenzo; Dones, Flavia; Mantovani, Giorgio; De Bonis, Pasquale; Rustemi, Oriela; Ricciardi, Luca; Cavallo, Michele Alessandro; Scerrati, Alba (Frontiers in Neurology, 2020)
Background:The possible influence of different antithrombotic drugs on outcome after neurosurgical treatment of chronic subdural hematoma(CSDH) is still unclear.Nowadays,no randomized clinical trials are available. A metanalysis including 24 studies for a total of 1812 pooled patients,concluded antiplatelets and anticoagulation present higher risk of recurrences. On the other hand,several studies highlighted that antithrombotic drugs suspension,timing of surgery and resumption of these drugs are still debated,concluding patients taking antithrombotic drugs present higher risk of thromboembolic events with no excess risk of bleed recurrence or worse functional outcome. Our assumption is that the real hemorrhagic risk related with antithrombotic drugs continuation in CSDH may be overrated and the thromboembolic risk discontinuation underestimated, especially in patients with high cardiovascular risk. Methods:A comprehensive Literature review with the search terms"acetylsalicylic acid”and “chronic subdural hematoma"was performed.Clinical status,treatment,time of drug discontinuation,complications(in particular re-bleeding or thromboembolic events)and clinical and radiological outcome at follow-up were evaluated. Results:Five retrospective studies were selected for the review, three of them reporting specifically low-dose acetylsalicylic intake and 2 of them general antithrombotic drugs for a total of 1226 patients.Only 2 papers reported the thromboembolic rate after surgery,in one paper it is not even divided from other cardiac complication. Conclusion: The Literature review does not clarify the best management of low-dose acetylsalicylic in CSDH patients, in particular concerning the balance between thromboembolic events rate and re-bleeding risks.We do believe CSDH precipitates the worsening of co-morbidities that cause an increased mortality.Further studies clearly evaluating the thromboembolic events are strongly needed to clarify this topic.